Structural Properties of Potential Synthetic Vaccine Adjuvants - TLR Agonists - Honegr, Jan; Soukup, Ondrej; Doležal, Rafael; Malinak, David; Penhaker, Marek; Prymula, Roman; Kuca, Kamil (Current medicinal chemistry, 2015)
Toll like receptors (TLRs) are a family of transmembrane proteins which play a key role in innate immunity. When TLRs come into contact with a potential threat, they initiate a signaling cascade leading to release of cytokines and chemokines, maturation of antigen presenting cells and immune activation. Molecules which can activate TLRs may be utilized for vaccine development and act as vaccine adjuvants. Adjuvants can facilitate production of more effective vaccines based on antigens produced by recombinant techniques or by DNA vaccines, which are often poorly immunogenic since they lack the endogenous innate immunostimulatory components of the pathogen. In this paper the structural properties of such prospective compounds are thoroughly discussed.
Keywords: Adjuvants, Immunologic; Animals; vztahy mezi strukturou a aktivitou; Molecular Structure; Vaccines, Synthetic; syntetické vakcíny; Structure-Activity Relationship; Toll-Like Receptors; molekulární struktura; lidé; zvířata; toll-like receptory; adjuvancia imunologická; Humans